Cover Picture: 3D Binary Mesocrystals from Anisotropic Nanoparticles (Angew. Chem. Int. Ed. 2/2022). Issue 2 (6th December 2021) - Jenewein, Christian; Avaro, Jonathan; Appel, Christian; Liebi, Marianne; Cölfen, Helmut
Abstract : Binary mesocrystals demonstrate the combination of nanocrystals from different materials within a highly ordered manner. While nanocubes appear to be simple in their geometry, they can arrange in various ways into a complex entity that not only directs its habitus but also its properties. In their Research Article (e202112461), Helmut Cölfen et al. report on the formation and structural analysis of micrometer‐sized two‐ and three‐dimensional binary particle assemblies, revealing their mesocrystalline nature and highlighting their importance within the growing field of metamaterials.